2013
DOI: 10.1021/jp405853j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Water Confined in Reversed Micelles: Multidimensional Vibrational Spectroscopy Study

Abstract: Here we perform a comprehensive study of ultrafast molecular and vibrational dynamics of water confined in small reversed micelles (RMs). The molecular picture is elucidated with two-dimensional infrared (2D IR) spectroscopy of water OH stretch vibrations and molecular dynamics simulations, bridged by theoretical calculations of linear and 2D IR vibrational spectra. To investigate the effects of intermolecular coupling, experiments and modeling are performed for isotopically diluted (HDO in D2O) and undiluted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
86
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 108 publications
8
86
1
4
Order By: Relevance
“…It is interesting to note that these results are quantitatively different than what is observed in (AOT and Igepal) reverse micelles 5,17,20,22,29,30,[71][72][73] where the OH (or OD) spectra are found to shift consistently to higher frequencies with increasing confinement (smaller reverse micelles). Fayer and co-workers have shown that this result can be understood in terms of a "shell" of interfacial water that exhibits blueshifted frequencies combined with a "core" waters away from the interface with a spectrum like that of bulk water.…”
Section: B Infrared (Ir) Lineshapescontrasting
confidence: 61%
“…It is interesting to note that these results are quantitatively different than what is observed in (AOT and Igepal) reverse micelles 5,17,20,22,29,30,[71][72][73] where the OH (or OD) spectra are found to shift consistently to higher frequencies with increasing confinement (smaller reverse micelles). Fayer and co-workers have shown that this result can be understood in terms of a "shell" of interfacial water that exhibits blueshifted frequencies combined with a "core" waters away from the interface with a spectrum like that of bulk water.…”
Section: B Infrared (Ir) Lineshapescontrasting
confidence: 61%
“…Such a core/shell model is certainly a simplification, and molecular dynamics simulations indeed show a gradual transition in reorientation time constant going from the surface to the core. 46,47 Nevertheless, our experimental results show that the distribution of reorientation times is approximately bimodal, as has been observed before for a wide range of reverse micellar systems, with both ionic and nonionic surfactants. [3][4][5][6][7][8][9][10][11][48][49][50] The total frequency-dependent complex permittivity (ω) of the reverse micellar system is thus modeled as a sum of the contributions of Igepal, core water, surface water, and cyclohexane…”
Section: B Dynamics Of Water In Nanoscopic Spheressupporting
confidence: 84%
“…Here, we show that local orientational order in liquids can be observed through its effect on the resonant transfer of vibrational excitations between the constituent molecules. Advances in ultrafast spectroscopy have made it possible to directly observe such intermolecular resonant vibrational energy transfer on surfaces [6], in clusters [7], in liquids [8][9][10][11][12][13][14][15][16][17], and in solids [18,19]. In these experiments, polarized optical excitation of a specific vibrational mode in part of the molecules creates an anisotropic distribution of excited transition-dipole moments, and resonant intermolecular transfer of the excitation causes this anisotropy to eventually vanish.…”
mentioning
confidence: 99%
“…In our calculation we assume that the energy transfer is incoherent (recent calculations on the OH-stretch resonant energy transfer in water suggest that this is a good approximation [20]) and caused by dipolar coupling, an approximation that has been validated by previous studies [6,7,[14][15][16]18,19], and that the vibrational line shape is homogeneous on the time scale of the energy transfer. Nondipolar effects [21], coherence [22], and spectral inhomogeniety [11][12][13] can all be incorporated in a straightforward manner to obtain more accurate results, but these effects do not influence our main conclusions.…”
mentioning
confidence: 99%